2020
DOI: 10.3389/fpsyg.2020.541766
|View full text |Cite
|
Sign up to set email alerts
|

Executive Search Consultants’ Biases Against Women (or Men?)

Abstract: Women remain under-represented in leadership positions in many countries. Since executive search consultants (also known as headhunters) act as gatekeepers in the hiring process, headhunters' biases might influence the female under-representation. There is preliminary evidence that suggests headhunters favor men, but direct evidence is missing. Thus, this study directly tested this assumption using implicit and explicit measures (an implicit association test and a gender role attitudes survey), completed by 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…This is comparable with Western studies: clients prefer men for managerial positions, as do some headhunters (Siegel et al., 2020) but rarely express this formally (Doldor et al., 2012; Tienari et al., 2013). In contrast to Chinese participants, the two Taiwanese participants reported that anti‐discrimination laws were well implemented and forbid gender and age discrimination.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This is comparable with Western studies: clients prefer men for managerial positions, as do some headhunters (Siegel et al., 2020) but rarely express this formally (Doldor et al., 2012; Tienari et al., 2013). In contrast to Chinese participants, the two Taiwanese participants reported that anti‐discrimination laws were well implemented and forbid gender and age discrimination.…”
Section: Resultssupporting
confidence: 83%
“…They are not incentivized to address inequality (Brands & Fernandez‐Mateo, 2017). Sometimes explicit biases are found (Siegel et al., 2020). Rejection by search firms can discourage women from applying for further jobs (Brands & Fernandez‐Mateo, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This style of leadership is more conditioned to the lack of security and independence in the fulfillment of work processes. Attempts to devalue or even relativize the positive valuations of female leadership appear as a way of maintaining male privileges [71]. Women, in fact, are sometimes classified by society as a delicate and sensitive gender, when in fact they can assume models or patterns of behavior usually attributable to men that prove to be more than adequate to achieve success in the labor market.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, we believe that headhunters have the power to perpetuate gender inequality in the company, but also the capacity to promote equality as the same way. So, headhunters are an ambivalent figure that, in some occasions, reproduce gender stereotypes and same-gender preferences, perpetuating gender inequality in business domain (Coverdill & Finlay, 1998;Gorman, 2005;Siegel et al, 2020); but in other occasions, acts as a change agent, promoting diversity and gender equality (Doldor et al, 2016;Fernández-Mateo & Fernández, 2016). From a gender perspective, the first question that raises about headhunter's activity it's what follows: if their decision and working process is focused on a subjective criterion based on their relationships with senior management, how does this fact affect professional women?…”
Section: Recruitment Systems and Headhunting: Gender Bias In Business...mentioning
confidence: 99%
“…Moreover, the majority of consultants in business are men. Thus, organizations interested in more women managers need to carefully consider who they hire as their executive search consultants (Siegel et. al, 2020).…”
Section: Preconceptions: the Ideal Executivementioning
confidence: 99%